Research and processing of shot blasting dust - S. L. Rovin; D. I. Kurach; S. V. Grigoriev (Литьë и металлургия, 2023)
Dispersed iron‑containing waste makes up the majority of solid technological waste of machine‑building and metallurgical enterprises. The problem of their disposal remains open, which leads to significant economic losses and creates a serious environmental threat. About 15–20 % of these wastes are assirative dusts of melting units. The content of compounds of various metals, and primarily iron, in some of them (for example, in the aspiration dust of arc steelmaking furnaces) reaches 60–70 % or more. However, today, despite all efforts, no more than 5–7 % of the captured aspiration dust of melting furnaces is used. One of the most significant problems of its disposal is the high dispersion (the size of the dust particles of arc furnaces, as a rule, does not exceed 50 microns) and the extreme heterogeneity and instability of the granulometric and chemical composition of the dust. Therefore, in most cases, attempts to use these dusts as a technological product: additives in molding and exothermic mixtures or non‑stick paints, coloring pigment in the production of building materials, modifying additives in the melting of foundry alloys, additives in the production of cement clinker, etc., ended at the level of experimental or pilot batches and were not essential for solving problems in general. The most promising direction of utilization of aspiration dusts is the recycling of metals contained in them. This article presents the results of studies of the composition and characteristics of aspiration dust of arc steelmaking furnaces of foundries of machine‑building plants, as well as the conditions of solid‑phase reduction and extraction of iron contained in it.